IL-17 and IFN-γ expression in lymphocytes from patients with active tuberculosis correlates with the severity of the disease - Jurado, Javier O. (2012)
Fil: Jurado, Javier O. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina